A Real-World, Non-interventional Indian Study Evaluating Intensive Plant-Based Butter Moisturizing Cream in Psoriasis - Hemangi Rajiv Jerajani; Jayakar Thomas; Alka Gupta; Gurram Narasimha Rao Netha; Ranju Chawla; Rashid Shaikh; Ravindra Babu; Irene Williams; Prajakta Talathi; Suyog C. Mehta; Rajan Mittal; Shivani Acharya; et al. (Adis, Springer Healthcare, 2019)
Abstract Introduction Psoriasis is estimated to affect 0.44-2.8% of the Indian population. Moisturizers are a key adjuvant psoriasis treatment strategy, but data regarding their effectiveness, safety and compliance pattern in an Indian context are lacking. Hence, this real-world study on an intensive plant-based butter moisturizing cream (Venusia ® Max) was conducted among Indian patients with psoriasis. Methods This was an observational, patient-reported outcomes (PRO) study in patients with psoriasis aged 18-75 years who were prescribed the cream in routine clinical practice, as per clinician's discretion, over 4 weeks. The primary outcome measure was improvement from baseline in quality of life assessed using the Dermatology Quality of Life Index (DLQI) at 4 weeks of the study period. The secondary outcome measures were improvement in dryness using the Dry Skin/Ichthyosis Area and Severity Index (DASI) score at 4 weeks, safety and compliance. The DLQI and DASI scores were recorded by the clinicians at baseline and after 2 (optional) and 4 weeks of starting the cream. Safety was assessed throughout the study. Results The study included 400 patients from 9 outpatient dermatology centers across India. Of 400 patients, 384 completed the study. A significant reduction in both the mean DLQI score (66.7%; p < 0.001) and mean DASI score (84.6%; p < 0.001) was observed at week 4 after starting the cream vs. baseline in the overall population. Overall, the cream showed a good safety and compliance profile during the study period. There were no serious adverse events or deaths. Conclusions The evidence from the PRO study suggests that use of the intensive plant-based butter moisturizing cream in a real-world scenario has a noticeable impact on improving the quality of life and reducing the skin dryness associated with psoriasis over 4 weeks. The moisturizing cream may serve as a valuable adjuvant treatment option for the management of psoriasis. Trial Registration Number CTRI/2017/03/008023. Funding Dr. Reddy's Laboratories Ltd.